INFLUENCE OF WAR ON CONSUMER BUYING BEHAVIOUR - Bulyk О.; Havryliuk І. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article is devoted to the study of the impact on consumer purchasing behaviour during the war. The authors of the research analyze factors influencing decisions on the purchase and determine that during the war these factors acquire a new meaning. The categories of goods that Ukrainians buy during the war are outlined, including: food, medicines, clothing and footwear, hygiene and care products, household chemicals, pet products, and products for children. It has been found that in times of war, consumers do not pay attention to the brand, but choose from what is available. Consumption was also affected by the displacement of many people to a safe place. The war has changed the lives of Ukrainians, including their consumption behaviour, due to reduced purchasing power, forced displacement and distribution difficulties. It was found that the population of Ukraine is currently experiencing the negative effects of the war, which affects their incomes and changes their health and safety needs. The demand for luxury goods is declining, while online shopping is growing. Intensification of the competitive processes in the conditions of uncertainty and the crisis caused by the war requires studying and understanding of the consumer psychology and the reasons that drive them to certain decisions. In the competitive economic system, a company must understand consumer behaviour to survive and thrive. Therefore, at this stage, manufacturers must understand the motivation behind customer choices and how each stage of the business responds to consumer needs. The study outlines the trends in the consumer segment, in particular, the rejection of expensive purchases; when buying food, purchases have become more conscious with more attention paid to the price, promotions and discounts; the choice of goods has become thoughtful – buyers have begun to analyse whether they need buying a product or they can do without it; the need to fit into the budget makes users spend more time online comparing different options.